Incidence of rheumatoid arthritis and muscloskeletal diseases in the elderly population (Tikrit Journal of Pharmaceutical Sciences, 2023)
The incidence of rheumatoid arthritis (RA) and muscloskeletal diseases was determined in random sample of 424 people aged 65 to 85 years. detailed clinical examinations were carried out in about two years between 2010-2011.a total of 3 men and 5 women fulfilled the 1987 American college of Rhumatology criteria for RA, so the incidence of RA was highest in subjects aged 65 years and tended to decline with age, no RA cases were found in men aged 80 years or more, the incidence of musceloskeletal diseases, defined as lack of an extremity or restriction of mobility in ajoint or the spine, was high in the highest aged group